A German exploration of Indian society: Ziegenbalgs "Malabarian Heathenism" ; an annotated English translation with an introduction and glossary - Ziegenbalg, Bartholomäus (The Mylapore Institute for Indigenous Studies [u.a.], 2006)
section 1. Background to Ziegenbalg's South Indian society -- section 2. Ziegenbalg's text -- section 3. Keys to the structure and meaning of the text -- section 4. Significance and limits of the text